Holistic and consumer-centric assessment of beer: A multi-measurement approach. (September 2017) - Jaeger, Sara R.; Cardello, Armand V.; Chheang, Sok L.; Beresford, Michelle K.; Hedderley, Duncan I.; Pineau, Benedicte
Abstract: Despite occupying a cornerstone position in consumer research and innovation, product liking/disliking provides only partial insight into consumer behaviour. By adopting a consumer-centric perspective and drawing on additional factors that underpin food-related consumer behaviour, a more complete product understanding is gained. The present research showcases this approach in a study with New Zealand beer (incl. pilsner, lager and ale categories). Implementation of a multi-variate approach with 128 regular beer drinkers provided assessments pertaining to liking and sensory novelty/complexity, situational appropriateness of consumption, as well as attitudes/perceptions and emotional associations. The 9 samples grouped into two clusters, where 4 of the beers were similar in being perceived as having less complex flavours, being appropriate for many uses and evoking stronger emotional associations of "relaxed/calm." The 4 beers were perceived as "easy to drink", and were, on average, most liked. One of the samples in this cluster was lighter in alcohol (2.5% ABV), but not inferior to beers with 4–5% ABV. The 5 beers in the second cluster were, on average, less liked and were associated with more negative emotions, e.g. "unhappy, "jittery", and "tense". Additional insights were gained from segmentation which identified two groups of consumers, named 'Lager Lovers' and 'Ale Aficionados'. Beers 1–4 were positively perceived by 'Lager Lovers' but less so by 'Ale Aficionados', and vice versa. The study was conducted under central location test conditions compatible with testing protocols often used in product research. The study protocol can be amended to include few/many consumer-centric measures and extended to product testing where packaging, brand, and other extrinsic information is available to consumers. Graphical abstract: Highlights: Consumers characterised beers using affective, attitudinal, situational and emotional measures. The data validate a multivariate consumer-based approach for the identification of unique products. Consumer segments existed with different product perceptions and preferences.